Proceedings of the 30th ACM International Conference on Information &Amp; Knowledge Management 2021
DOI: 10.1145/3459637.3482226
|View full text |Cite
|
Sign up to set email alerts
|

AdaGNN

Abstract: Graph Neural Networks have recently become a prevailing paradigm for various high-impact graph analytical problems. Existing efforts can be mainly categorized as spectral-based and spatialbased methods. The major challenge for the former is to find an appropriate graph filter to distill discriminative information from input signals for learning. Recently, myriads of explorations are made to achieve better graph filters, e.g., Graph Convolutional Network (GCN), which leverages Chebyshev polynomial truncation to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…To alleviate this issue, we introduce a diverse spectral filtering (DSF) framework to enhance spectral GNNs with trainable diverse filters. It is worth noting that though both JacobiConv [42] and AdaGNN [12] learn multiple filters in a seemingly similar way, they are essentially different from our method in nature. Concretely, their adaptive filters are mainly for studying each feature channel independently, whilist our diverse filters aim at individual context modeling for each node.…”
Section: Related Work 21 Spectral Graph Neural Networkmentioning
confidence: 87%
See 2 more Smart Citations
“…To alleviate this issue, we introduce a diverse spectral filtering (DSF) framework to enhance spectral GNNs with trainable diverse filters. It is worth noting that though both JacobiConv [42] and AdaGNN [12] learn multiple filters in a seemingly similar way, they are essentially different from our method in nature. Concretely, their adaptive filters are mainly for studying each feature channel independently, whilist our diverse filters aim at individual context modeling for each node.…”
Section: Related Work 21 Spectral Graph Neural Networkmentioning
confidence: 87%
“…Recent studies have shown that most spectral GNNs operate as polynomial spectral filters [9,20,42] with either fixed designs such as GCN [24], APPNP [15], and GNN-LF/HF [51] or learnable forms, e.g., ChebNet [11], AdaGNN [12], GPR-GNN [9], ARMA [5], Bern-Net [20], and JacobiConv [42]. Further remarks can be found in Appendix A.…”
Section: Related Work 21 Spectral Graph Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The major applications of GNN in SR are models based on Graph Convolutional Networks (GCN) [30][31][32] and Graph Attention Networks (GAT) [33]. These models use the information propagation mechanism to capture higher-order relationships between nodes and obtain the influence of different neighboring nodes to form the final representation for recommendation tasks [34,35]. Depending on how the data is modeled, GNN applications can be assigned to two categories.…”
Section: Graph Neural Networkmentioning
confidence: 99%
“…To address this issue, several GNN designs have been proposed that are specifically tailored for heterophilic graphs. These designs include MixHop [50], MM-DAN [51], BeyondGNN [32], AdaGNN [52], Beyond-GCN [53], and Geom-GCN [54]. Persistent curvature descriptors have been shown to be effective in representing protein-ligand complexes, but they rely on prior knowledge.…”
Section: Heterophily-based Gnnsmentioning
confidence: 99%